SIKAP ASEAN TERHADAP PELANGGARAN HAM DI MYANMAR PASCA KUDETA - Ambarwati Ambarwati (Jurnal Ilmiah Dinamika Sosial, 2022)
This paper analyzes ASEAN’s attitude toward human rights violence in Myanmar in the post February  2021 military coup. In many cases, ASEAN is often regarded in the dilemmatic position in taking attitude toward human rights violence, a dilemma between consistency in non-interference principle and protection of human rights (responsibility to protect / R2P). ASEAN has a principle of non-interference as a code of conduct in interaction between its members in accordance with Treaty and Amity of Cooperation (TAC). This principle is also applied regarding human rights violence in Myanmar, so that ASEAN is regarded as indecisive and weak. The problem of human rights violence is managed with a dialogue and avoid interventionist way as Western countries do.The method used in this paper is an analysis of descriptive qualitative with exploration some concepts, such as sovereignty, human rights, and responbility to protect. Focused actor in this paper is ASEAN as regional organization and what is to prove in this analysis is that the principle of non-interference is a not weak point of ASEAN, but it is a consistency in its attitude. The organization has been managing its members to respect each other sovereignty in their interactions for 54 years.